Proteomic analysis reveals that sugar and fatty acid metabolisms play a central role in sterility of the male-sterile line 1355A of cotton - Wu, Yuanlong (J Biol Chem, 2019)
Cotton (Gossypium spp.) is one of the most important economic crops and exhibits yield-improving heterosis in specific hybrid combinations. The genic male-sterility system is the main strategy used for producing heterosis in cotton. To better understand the mechanisms of male sterility in cotton, we carried out two-dimensional electrophoresis (2-DE) and label-free quantitative proteomics analysis in the anthers of two near-isogenic lines, the male-sterile line 1355A and the male-fertile line 1355B. We identified 39 and 124 proteins that were significantly differentially expressed between these two lines in the anthers at the tetrad stage (stage 7) and uninucleate pollen stage (stage 8), respectively. Gene ontology-based analysis revealed that these differentially expressed proteins were mainly associated with pyruvate, carbohydrate, and fatty acid metabolism. Biochemical analysis revealed that in the anthers of line 1355A, glycolysis was activated, which was caused by a reduction in fructose, glucose, and other soluble sugars, and that accumulation of acetyl-CoA was increased along with a significant increase in C14:0 and C18:1 free fatty acids. However, the activities of pyruvate dehydrogenase and fatty acid biosynthesis were inhibited and fatty acid β-oxidation was activated at the translational level in 1355A. We speculate that in the 1355A anther, high rates of glucose metabolism may promote fatty acid synthesis to enable anther growth. These results provide new insights into the molecular mechanism of genic male sterility in upland cotton.